2019
DOI: 10.7554/elife.43584
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced tau filaments are polymorphic and differ from those in Alzheimer’s and Pick’s diseases

Abstract: Assembly of microtubule-associated protein tau into filamentous inclusions underlies a range of neurodegenerative diseases. Tau filaments adopt different conformations in Alzheimer’s and Pick’s diseases. Here, we used cryo- and immuno- electron microscopy to characterise filaments that were assembled from recombinant full-length human tau with four (2N4R) or three (2N3R) microtubule-binding repeats in the presence of heparin. 2N4R tau assembles into multiple types of filaments, and the structures of three type… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
447
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 369 publications
(487 citation statements)
references
References 77 publications
34
447
6
Order By: Relevance
“…The hairpin-like structure of β4-β7 in the CBD fold resembles that of β3-β6 in the Pick fold, with the exception of C322, which points inwards to form the sharp turn in the CBD fold, and which points outwards in the Pick fold. Interestingly, in all four tau filament folds from human brain, β-strands are formed by approximately the same residues ( Figure 3); this is also true of tau filaments assembled in vitro using heparin (37). It suggests a model for the diversity of tau folds, where β-strands form fixed building blocks and the loops and turns between strands provide diversity.…”
mentioning
confidence: 79%
“…The hairpin-like structure of β4-β7 in the CBD fold resembles that of β3-β6 in the Pick fold, with the exception of C322, which points inwards to form the sharp turn in the CBD fold, and which points outwards in the Pick fold. Interestingly, in all four tau filament folds from human brain, β-strands are formed by approximately the same residues ( Figure 3); this is also true of tau filaments assembled in vitro using heparin (37). It suggests a model for the diversity of tau folds, where β-strands form fixed building blocks and the loops and turns between strands provide diversity.…”
mentioning
confidence: 79%
“…and 2N4R Tau vary in their architecture (Zhang et al, 2019). The ordered core of 2N3R Tau fibrils comprises the R3 repeat of two parallel Tau molecules, whereas 2N4R Tau fibrils adopt several conformations with a core consisting of R2 and R3 β strands of the same molecule (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…and 2N4R Tau vary in their architecture (Zhang et al, 2019). The ordered core of 2N3R Tau fibrils comprises the R3 repeat of two parallel Tau molecules, whereas 2N4R Tau fibrils adopt several conformations with a core consisting of R2 and R3 β strands of the same molecule (Zhang et al, 2019). Intriguingly, these differences in fibril architecture may lead to a different stability of 3R and 4R Tau fibrils, which may explain their varying susceptibility to the human Hsp70 disaggregation machinery.…”
Section: Discussionmentioning
confidence: 99%
“…This could possibly explain the drastic decrease in the aggregation This clearly indicates the cumulative effect of the three phosphorylation sites on the inhibition of fibrillization. It is noteworthy that despite the fact that the R1 repeat is not part of the core of ex vivo filaments 39 , several studies have consistently shown that sequence motifs within these region associated with disease-associated mutations 40 , PTMs 41 or other sequence perturbations significantly alter the kinetics and aggregation properties of tau. Our results show that phosphorylation within the MTBD inhibits tau fibril formation, which is contrary to the conventional wisdom that this enhances tau aggregation and fibrillization.…”
Section: Discussionmentioning
confidence: 99%